2021
DOI: 10.3389/fimmu.2021.636954
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Activate Proinflammatory Functions of Human Neutrophils

Abstract: Neutrophil extracellular traps (NETs) consist of decondensed nuclear chromatin that is associated with proteins and are released by neutrophils during an inflammatory response. Released NETs are able to capture pathogens, prevent their dissemination and potentially kill them via antimicrobial peptides and proteins that are associated with the decondensed chromatin. In addition to their antimicrobial functions, NETs have also been shown to exert immunomodulatory effects by activation and differentiation of macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 49 publications
1
82
0
2
Order By: Relevance
“…However, there is some evidence that neutrophils and NETs also exert reparative effects in the context of tumor inflammation [ 198 , 213 ]. Moreover, recent studies indicate that different components of NETs can propagate [ 245 , 246 ] or modulate inflammation [ 247 ]. Such dichotomy in the outcome of neutrophil activity is fascinating and intriguing [ 282 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is some evidence that neutrophils and NETs also exert reparative effects in the context of tumor inflammation [ 198 , 213 ]. Moreover, recent studies indicate that different components of NETs can propagate [ 245 , 246 ] or modulate inflammation [ 247 ]. Such dichotomy in the outcome of neutrophil activity is fascinating and intriguing [ 282 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates that NETs can promote inflammation by inducing proinflammatory cytokines from different immune cells [ 245 , 246 ]. In particular, histones, the major citrullinated proteins in NETs, activate the transcription of IL-1β in mononuclear cells by binding and activating TLR4.…”
Section: Nets Modulate Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…But could AAT have effects in other cell types that are beneficial in the context of TB? One possibility is that AAT antagonizes the damaging effects of neutrophils in the later stages of TB (Lowe et al, 2012) by: (i) sequestering IL-8 (Bergin et al, 2010), inhibiting neutrophil chemotaxis (McCarthy et al, 2016), and, as we have shown, inhibiting IL-8 production via binding to GR and (ii) inhibiting formation of neutrophil extracellular traps (NETs) -which are elastase-and IL-8induced extruded DNA decorated with citrullinated histones, elastase, and other proteinsmeant to capture extracellular bacteria but may also contribute to tissue injury (de Melo et al, 2018;Dömer et al, 2021;Frenzel et al, 2012;Wartha et al, 2007). AAT has also been shown to cause decreased shedding of macrophage mannose receptors (MMR), increasing their cell surface expression and reducing soluble MMR, effects which may contribute to the antiinflammatory effects of AAT (Embgenbroich et al, 2021;Serban et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…ICs are powerful stimuli of NET release (e.g., [ 22 , 67 , 68 ). In addition, NETs stimulate neutrophils to produce further NETs and to secrete IL‐8 and BAFF [ 69] , promoting the vicious circle between B cells and neutrophils (Figure 1 ).…”
Section: Netsmentioning
confidence: 99%